2021
DOI: 10.3390/app11041596
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Sulfate Adsorption on Modified Adsorbents Prepared from Zea mays Stems

Abstract: The effect of temperature on the sulfate adsorption capacity of adsorbents prepared from corn stalks (Zea mays) was evaluated. Two bioadsorbents were prepared from biomass: a biochar modified with H2SO4 with mass: volume ratio 1:1 (B 1:1), and cellulose modified with cetyl trimethyl ammonium chloride (CTAC). There were also determined thermodynamic parameters (ΔG°, ΔS° and ΔH°) and it was studied the adsorption kinetics and isotherm. At 25 °C was obtained the highest adsorption capacity of 16.4 and 7.4 mg/g wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Earlier studies also reported the suitability of Freundlich isotherms to account for the adsorption of Zn 2+ on biochars from typical Vietnamese plant residues, 39 that of Cu 2+ on both rice husks- and olive pomace-derived biochars, 40 that of Fe 2+ on Conocarpus sp. biochar 41 and that of S 42 onto maize straw biochar.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies also reported the suitability of Freundlich isotherms to account for the adsorption of Zn 2+ on biochars from typical Vietnamese plant residues, 39 that of Cu 2+ on both rice husks- and olive pomace-derived biochars, 40 that of Fe 2+ on Conocarpus sp. biochar 41 and that of S 42 onto maize straw biochar.…”
Section: Resultsmentioning
confidence: 99%
“…In 2016, the SO 4 2− concentration in both lakes was highly elevated, which could have resulted from the direct wastewater discharge from several industries [48]. However, SO 4 2− levels improved significantly in 2021.…”
Section: Discussionmentioning
confidence: 98%
“…11 However, efficient treatment of sulfides remains a challenge. Sources of sulfate in sewage include background levels in drinking water sources, 12 household detergents, 13 industrial discharges, 14 and infiltration of seawater into sewers in coastal areas. In addition to their strong odor, sulfides exert significant chlorine or chloramine demand and HS − strongly absorbs ultraviolet (UV) light ( ε 254 = 950 M −1 cm −1 (ref.…”
Section: Introductionmentioning
confidence: 99%